A novel UHMWPE anchor for improving the pullout resistance of pedicle screws - Lin, Che-Kuang; Jaw, Fu-Shan; Young, Tai-Horng (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionThe ability to maintain bone purchase and resist pullout is considered a basic requirement for pedicle screws. However, poor bone density or oversized pilot holes can increase the risk of screw loosening and pullout. Our team developed a novel UHMWPE anchor that attaches to the proximal portion of the pedicle screw to improve engagement with the bone, even in conditions with poor bone quality or large pilot holes.MethodsSynthetic bone blocks simulating normal bone density (15 PCF) and osteoporotic bone (10 PCF) were used to investigate the pullout strength of anchored pedicle screws and traditional pedicle screws. Five screw constructs were evaluated: (A) 4.0 mm pedicle screw and 3.0 mm pilot hole; (B) 4.0 mm pedicle screw with a 4.0 mm anchor and 3.0 mm pilot hole; (C) 4.0 mm pedicle screw with a 4.0 mm anchor and 3.2 mm pilot hole; (D) 4.0 mm pedicle screw and 3.2 mm pilot hole; (E) 5.0 mm pedicle screw and 3.2 mm pilot hole.ResultsThe anchor-based 4.0 mm screw with a 3.0 mm pilot hole (group B) had the highest pullout strength among all groups, both in normal bone and osteoporotic bone. Even when using a larger 3.2 mm pilot hole, the pullout strength of the anchored 4.0 mm screw was within 90% of the values recorded with the 3.0 mm pilot hole. Notably, the average pullout strength of the 4.0 mm pedicle screw with anchor was higher than the 5.0 mm pedicle screw without an anchor in both bone densities.ConclusionThe results of this study demonstrate that the novel anchor can significantly increase the pullout strength of pedicle screws. The anchor also allows for more flexibility when selecting a screw size, especially when the insertion space is limited.